2003
DOI: 10.1148/radiol.2291021033
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Arteries: Contrast-enhanced MR Imaging with SH L 643A—Experience in 12 Volunteers

Abstract: SH L 643A causes significant improvement of the blood-myocardium contrast enhancement at coronary MR angiography compared with that with nonenhanced sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 35 publications
0
39
1
2
Order By: Relevance
“…Dendrimers such as polyamidoamine (PAMAM) [1], polyethyleneimine (PEI) [2] and poly(Llysine) (PLL) [3] have been used to facilitate delivery and expression of DNA [4], delivery of drugs and radiotherapeutics [5,6] and for in vitro and in vivo diagnostics [7]. Dendrimers are synthesized by either divergent [8] or convergent [9] approaches, each of which can give rise to linear or branched architectures, thus enabling the size and generation of the dendrimer to be controlled during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers such as polyamidoamine (PAMAM) [1], polyethyleneimine (PEI) [2] and poly(Llysine) (PLL) [3] have been used to facilitate delivery and expression of DNA [4], delivery of drugs and radiotherapeutics [5,6] and for in vitro and in vivo diagnostics [7]. Dendrimers are synthesized by either divergent [8] or convergent [9] approaches, each of which can give rise to linear or branched architectures, thus enabling the size and generation of the dendrimer to be controlled during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Gadomer®-17 ( Fig. 8), a dendrimer comprising a trimesoyl triamide core and polylysine dendritic branching with terminal payloads of Gd-DTPA [68], is the first dendrimer-based product to be clinically evaluated as a contrast agent for magnetic resonance angiography [69,70]. It has high vascular permeability, and is able to visualize intratumoral vasculature [71] and acute myocardial ischemia [72].…”
Section: Figurementioning
confidence: 99%
“…Raman et al [29] compared gadofoveset (0.03 mmol/kg), an intravascular contrast agent, to Gd-BOPTA (0.1 mmol/kg), an extracellular agent, for free-breathing 3D coronary MRA and reported that use of the intravascular contrast agent performed as well as, or slightly better than, the extracellular contrast agent at 3 T. Slightly albumin-binding contrast medium combines the benefits of both extracellular and intravascular agents as it remains in the blood for a relatively prolonged time with greater T1 shortening effect while maintaining late enhancement abilities [36,37]. Several studies have agreed on the ability of intravascular or slightly albumin-binding agents to improve arterial contrast on 3D gradient echo coronary MRA, particularly when used with an inversion-recovery pre-pulse [38][39][40][41][42].…”
Section: Contrast Mediummentioning
confidence: 99%